Analysis of the Factors that Influence the Academic Performance of Financial Accounting Students using Binary Choice Models - Ballester, Carmen Pilar Martí (Review of Business Management, 2012)
The member states of the European Union, including Spain, show a high level of school failure and/or drop-outs, meaning a higher unitary cost per university student and, therefore, a higher public expenditure allocated to university education. Consequently, knowing the factors determining students’ success rates in the academic disciplines they have applied for will allow administrators to improve teaching quality and to decrease education costs. Therefore, the object of this research is to examine the effect of demographic, institutional, economic and academic factors on students’ academic performance. The study of these factors is conducted through the Walberg educational productivity model (1981), which is based on the cognitive learning theory. In order to reach this objective, there is a database containing integrated information on 698 students enrolled during the 2009/2010 academic year in the financial accounting faculty at UAB, on which binary selection models are applied. Results show that the university access grade, classes taken by students, gender, previous studies, time spent by professors at the university and the hours when students attend the university have an impact on students’ academic performance. These results are in line with previously obtained empirical proof. Based on these results it was possible to suggest several recommendations to administrators and professors to improve management of the financial accounting academic discipline. Key words: Academic performance. Accounting. Logit model. Probit model.